A label-free electrochemical affisensor for cancer marker detection: the case of HER2 - Ravalli, Andrea; Rocha, Carolina Gomes da [UNESP]; Yamanaka, Hideko [UNESP]; Marrazza, Giovanna (Elsevier B. V., 2015)
In this paper, we report the development of a sensitive label-free impedimetric biosensor based on the use of affibody as bioreceptor and gold nanostructured screen-printed graphite as a sensor platform for the detection of human epidermal growth factor receptor 2 (HER2). The affisensor is realized by immobilizing a terminal cysteine-modified affibody on gold nanoparticles. The sensor was characterized by electrochemical techniques and scanning electron microscopy (SEM). Furthermore, surface plasmon resonance (SPR) technology was also applied to explore the potential of affibodies as small-molecule discriminating tools. Using optimized experimental conditions, a single-use affisensor showed a good analytical performance for HER2 detection from 0 to 40μg/L. The estimated limit of detection was 6.0μg/L. Finally, the realized affisensor was applied to human serum samples.
Keywords: Affibody; Biosensor; Her2; Nanoparticle; Tumor marker